Bevel-geared mechanical foot: a bioinspired robotic foot compensating yaw moment of bipedal walking. (3rd July 2022) - Chen, Tsung-Yuan; Shigaki, Shunsuke; Hosoda, Koh
Abstract : The human foot structure has been evaluated, especially on its contribution to stable bipedal locomotion. This paper presents a bevel-geared mechanical bioinspired robotic foot that emulates the rotational motions of the human subtalar and oblique midtarsal joints. The motions generate a yaw moment at touch-down and may contribute to suppressing yaw rotation of the whole body. We develop a musculoskeletal biped robot equipped with feet and conduct walking experiments to measure the generated yaw moment during walking. Experimental results demonstrate that the peak of the yaw moment and the amplitude change of the torso yaw rotation significantly decrease by 41.4% and 13.0% with the geared foot, respectively. This study proposes a mechanical design for reducing the yaw moment and whole-body rotation of a bipedal walking robot without complicated control. GRAPHICAL ABSTRACT: UF0001